Peran Komite Sekolah Untuk Menigkatkan Mutu Pendidikan - Andelia, Shanty Okta (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2023)
The formation of school committees in education units or city and district governments is part of the implementation of school-based management or SBM, which was definitely implemented before, according to the Minister of Education Decree number 044/2002. In school-based management, according to the Ministry of National Education 2001, it is basically a model. management that can provide greater autonomy to schools and can encourage participatory decision-making and directly involve all school members, both student teachers and school principals, employees or parents and the community, therefore to improve the quality of schools based on national education policies. As well as the school committee also in relation to education has many important roles as a supporter, of course, from these various roles that can have a lot of influence on the sustainability of education in Indonesia so far, including being able to improve the quality of education from the existence of this school community can generate a lot of opinion from the public public or the community and the teacher over the school in particular, therefore in writing this paper the writer will examine the role and influence of the school community which supports improving the quality of education from various opinions about school committees in Indonesia